Potential effect of chloroquine and propranolol combination to treat colorectal and triple-negative breast cancers - Anselmino, L. E. (2023)
Drug repositioning explores the reuse of non-cancer drugs to treat tumors. In this work, we evaluated the effect of the combination of chloroquine and propranolol on colorectal and triple-negative breast cancers. Using as in vitro models the colorectal cancer cell lines HCT116, HT29, and CT26, and as triple-negative breast cancer models the 4T1, M-406, and MDA-MB-231 cell lines, we evaluated the effect of the drugs combination on the viability, apoptosis, clonogenicity, and cellular migratory capacity. To explore the in vivo effects of the combination on tumor growth and metastasis development we employed graft models in BALB/c, nude, and CBi mice. In vitro studies showed that combined treatment decreased cell viability in a dose-dependent manner and increased apoptosis. Also, we demonstrated that these drugs act synergically and that it affects clonogenicity and migration. In vivo studies indicated that this drug combination was effective on colorectal models but only partially on breast cancer. These results contributed to the search for new and safe treatments for colorectal and triple-negative carcinomas.